(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article delves into the intricacies of translating idioms and colloquial expressions, illuminating the challenges translators encounter in accurately conveying the intended meaning, cultural implications, and subtleties of these expressions. This paper investigates how idiomatic idioms' context dependence, language obstacles, and cultural differences affect translation. Because of the intrinsic cultural and linguistic nuances incorporated into these language features, translating idioms and colloquial expressions can be exceptionally challenging for translators. It also covers the methods translators use to accurately capture the spirit of idioms and colloquialisms while preserving linguistic integrity and cultural authenticity. This article seeks to shed light on these difficulties and offer insights into the complex craft of translating idioms and colloquial terms providing insightful viewpoints for language experts and translation studies scholars.